1997
DOI: 10.1029/97gl01978
|View full text |Cite
|
Sign up to set email alerts
|

Source mechanisms of the 1944 Tonankai and 1946 Nankaido earthquakes: Spatial heterogeneity of rise times

Abstract: Kanarnori [ 1972].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…This estimate is within the range of M s 8.0–8.3 estimated from surface waves by Kanamori [1972] and M j 8.0 and comparable with the M L 8.3 obtained by Richter [1958]. Recent inversions of combined tsunami waveforms and geodetic data by Kato and Ando [1997] and Tanioka and Satake [2001] resulted in seismic moment estimates of 2.0–2.8 × 10 28 dyn cm ( M w 8.2–8.23).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This estimate is within the range of M s 8.0–8.3 estimated from surface waves by Kanamori [1972] and M j 8.0 and comparable with the M L 8.3 obtained by Richter [1958]. Recent inversions of combined tsunami waveforms and geodetic data by Kato and Ando [1997] and Tanioka and Satake [2001] resulted in seismic moment estimates of 2.0–2.8 × 10 28 dyn cm ( M w 8.2–8.23).…”
Section: Discussionsupporting
confidence: 86%
“…A large 4.48‐m slip patch on the shallow portion of the southeast edge has a risetime of 9 min, which cannot be resolved with seismic records due to its extremely long risetime. Kato and Ando [1997] attributed this to a relaxation barrier that may have stopped or slowed rupture. The fit between the synthetic and observed tsunami waveforms and the geodetic deformation in the Kato and Ando study are not markedly improved, with only 12% variance reduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean slip is identical to the case of Figure 5, such that M w 9.14. excess moment release (reckoned to 1 day after the earthquake) for the 2004 Sumatra-Andaman earthquake in comparison to seismic moment estimates. There have been suggestions from studies of previous earthquakes that short-term afterslip may occur at time periods that affect tsunami generation (Kikuchi et al, 1993;Heki and Tamura, 1997;Kato and Ando, 1997;Mazzotti et al, 2000;Miyazaki et al, 2004). For tsunami earthquakes in particular, long source duration is often ascribed to both anomalously low rupture velocities and slow slip rates (Kanamori, 1972;Kikuchi and Kanamori, 1995).…”
Section: Temporal Earthquake Rupture Processesmentioning
confidence: 95%
“…It seems likely that the strong motion records reflect the much shorter period component of the fault slip than that affecting the tsunami generation. Kato and Ando (1997) analyzed the tsunami data considering the finite rise time of the crustal motion, and found that a large tsunami with a rise time of as long as a few minutes was excited around the Atsumi peninsula. This region is just outside the coseismic slip region (asperity) obtained in the present analysis.…”
Section: Seismic Moment and Possible Slow Slipmentioning
confidence: 99%